Optimalisasi Verifikasi dan Validasi DTKS Desa Kepanjen Kecamatan Gumukmas Kabupaten Jember - Ari Septianingtyas Purwandhini; Ragilia Fajar Rizki; Amira Yusrillia Salsabella; Ratih Kartika Bunga; Yeri Kuniawan; Lintang Adedari (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2022)
The social welfare of the community, especially in Kepanjen Village, was still very low. This is indicated by the low income of the community. In addition, many people in Kepanjen Village do not have permanent jobs, which results in uncertain income and uncertain economic conditions for the community. It is hoped that the social assistance program that is currently being promoted by the government can be right on target to people who really need it. Problems that are still often faced by rural communities today are related to social welfare. The condition of underprivileged people is still commonly found in Kepanjen Village. So far, the government has used the Social Welfare Integrated Data (DTKS) published by the Ministry of Social Affairs as a reference in determining who is entitled to the various social assistance protection programs. But often the assistance provided by the government is not on target. Therefore, to support whether the assistance is on target, the local government is assisted by several related parties to verify and validate DTKS. With this enumerator it is hoped that it can help optimize the DTKS verification and validation process in order to achieve the 4 stages of data use.